Workshop Pengembangan Media Ajar Interaktif Berbasis Canva dan Flipbook: Program KKN-Dik Unismuh Makassar - Nurasma, Nurasma; Arumdani, Arsy; Nasir, Nasir; Surianty, Surianty (LPPM Universitas Al Muslim, 2025)
The Community Service Program on Education (KKN-Dik) is a program that aims to help teachers improve their skills in developing interactive learning media. This activity was held on October 5, 2024 at the Teacher Activity Unit Center (PUKG) of Balusu District, Barru Regency, involving 54 teachers from various partner schools. This community service activity aimed to improve teachers' knowledge and skills through the development of canva-based interactive teaching media to design teaching materials and flipbooks in the creation of interactive digital books so that the visuals of the material displayed are more attractive. The method of implementing the activity is in the form of learning by doing which included discussion, practice, and direct mentoring. The results of this activity showed a significant improvement in the ability of teachers to utilize the two learning media, especially taking advantage of the available features. Participants also gave positive responses to this activity because it was relevant to their needs. Thus, it is hoped that it can improve the quality of learning, strengthen the role of teachers, and create a more interesting learning experience for students. Therefore, this activity should be carried out regularly to strengthen teachers' ability to use interactive learning media.